2013
DOI: 10.1002/jcb.24489
|View full text |Cite
|
Sign up to set email alerts
|

Topology, glycosylation and conformational changes in the membrane domain of the vacuolar H+‐ATPase a subunit

Abstract: Published topological models of the integral membrane a subunit of the vacuolar proton-translocating ATPase complex have not been in agreement with respect to either the number of transmembrane helices within the integral membrane domain, or their limits and orientations within the lipid bilayer. In the present work we have constructed a predictive model of the membrane insertion of the yeast a subunit, Vph1p, from a consensus of seven topology prediction algorithms. The model was tested experimentally using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 48 publications
5
21
0
Order By: Relevance
“…This model is based on a synthesis of data derived from cryo-EM 3D reconstruction, evolutionary covariance mapping of key residues, and low resolution X-ray crystallography. It confirms that the a subunit membrane domain consists of 8 TMs, as has been previously shown (2,12), with TM7 and TM8 highly tilted and forming an interface with the V0 rotor c-ring that enables proton translocation at the a subunit/c-ring interface.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…This model is based on a synthesis of data derived from cryo-EM 3D reconstruction, evolutionary covariance mapping of key residues, and low resolution X-ray crystallography. It confirms that the a subunit membrane domain consists of 8 TMs, as has been previously shown (2,12), with TM7 and TM8 highly tilted and forming an interface with the V0 rotor c-ring that enables proton translocation at the a subunit/c-ring interface.…”
supporting
confidence: 84%
“…We have shown ELII is the site of N-glycosylation within subunit a1-a4 (25,26) indicating that ELII is luminal/extracellular. In contrast, we and others have shown that the C-terminal domain is cytoplasmic (12,25,26).Comparing the accessibility of either epitope in permeabilized vs nonpermeabilized cells can determine if a4 is expressed on the cell surface. In permeabilized cells, one would expect that both cytoplasmic and extracellular epitopes would be assessable to fluorescently-labeled antibodies; in nonpermeabilized cells, only HA on the extracellular EL2, would be available.…”
Section: G820rmentioning
confidence: 77%
See 2 more Smart Citations
“…Nevertheless, we have shown here that in the pat2-1 mutant, lacking the b-subunit of the AP3 complex (Feraru et al, 2010), VHA-a3 and AVP1/VHP1 still reach their destination pointing to the existence of a third route to the tonoplast of the LV that might completely bypass the Golgi apparatus. Although mammalian isoforms of subunit a have been shown to be modified by N-glycosylation (Kartner et al, 2013), VHA-a3 lacks predicted N-glycosylation sites and passage through the Golgi is thus not required.…”
Section: Discussion Traffic Routes To the Tonoplastmentioning
confidence: 99%